Prediction of Perinatal and Neurodevelopmental Outcomes in Newborns with a Birth Weight below the 3rd Percentile: Performance of Two International Curves - Prospective Cohort from a Brazilian City - Marcos Masaru Okido; Ricardo de Carvalho Cavalli; Viviane Cunha Cardoso; Alessandra Cristina Marcolin (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objectives To evaluate the performance of Intergrowth-21 st (INT) and Fetal Medicine Foundation (FMF) curves in predicting perinatal and neurodevelopmental outcomes in newborns weighing below the 3rd percentile. Methods Pregnant women with a single fetus aged less than 20 weeks from a general population in non-hospital health units were included. Their children were evaluated at birth and in the second or third years of life. Newborns (NB) had their weight percentiles calculated for both curves. Sensitivity, specificity, positive (PPV) and negative predictive value (NPV), and area under the ROC curve (ROC-AUC) for perinatal outcomes and neurodevelopmental delay were calculated using birth weight < 3rd percentile as the cutoff. Results A total of 967 children were evaluated. Gestational age at birth was 39.3 (± 3.6) weeks and birth weight was 3,215.0 (± 588.0) g. INT and FMF classified 19 (2.4%) and 49 (5.7%) newborns below the 3rd percentile, respectively. The prevalence of preterm birth, tracheal intubation >24 hours in the first three months of life, 5th minute Apgar <7, admission to a neonatal care unit (NICU admission), cesarean section rate, and the neurodevelopmental delay was 9.3%, 3.3%, 1.3%, 5.9%, 38.9%, and 7.3% respectively. In general, the 3rd percentile of both curves showed low sensitivity and PPV and high specificity and NPV. The 3rd percentile of FMF showed superior sensitivity for preterm birth, NICU admission, and cesarean section rate. INT was more specific for all outcomes and presented a higher PPV for the neurodevelopmental delay. However, except for a slight difference in the prediction of preterm birth in favor of INT, the ROC curves showed no differences in the prediction of perinatal and neurodevelopmental outcomes. Conclusion Birth weight below the 3rd percentile according to INT or FMF alone was insufficient for a good diagnostic performance of perinatal and neurodevelopmental outcomes. The analyzes performed could not show that one curve is better than the other in our population. INT may have an advantage in resource contingency scenarios as it discriminates fewer NB below the 3rd percentile without increasing adverse outcomes.